One Year of Coronavirus Disease 2019 (COVID-19) in Brazil: A Political and Social Overview - Matheus Negri Boschiero; Camila Vantini Capasso Palamim; Manoela Marques Ortega; Renan Marrichi Mauch; Fernando Augusto Lima Marson (Ubiquity Press, 2021)
Background: Coronavirus Disease 2019 (COVID-19) became the deadliest pandemic of the new millennium. One year after it became a pandemic, the current COVID-19 situation in Brazil is an example of how the impacts of a pandemic are beyond health outcomes and how health, social, and political actions are intertwined. Objectives: We aimed to provide an overview of the first year of the COVID-19 pandemic in Brazil, from a social and political point of view, and to discuss the perspectives from now on. Methods: This is a narrative review using official, scientific (PubMed, Medline, and SciELO databases) and publicly available data. Press articles were also used that contain important information not found in these databases. Findings: We address the impacts of COVID-19 in different regions of Brazil, on indigenous populations, health care workers, and how internal social contrasts impacted the pandemic's advance across the country. We also discuss key points that culminated in the country's failed management of the COVID-19 spread, such as poor management of the public health care system, disparities between public and private health care infrastructure, lack of mass testing and viral spread tracking, lack of preparedness and planning to implement strict isolation and social distancing measures, and, most importantly, political instability, a deteriorating Health Ministry and sabotaging attitudes of the country's president, including anti-scientific actions, underplaying COVID-19 severity, spreading and powering fake news about the pandemic, promoting knowingly inefficient medications for COVID-19 treatment, and interference in collective health policies, including the country's vaccination plan. Conclusions: After one year of COVID-19 and a disastrous management of the disease, Brazil has more than 11 million cases, 270,000 deaths, and the highest number of daily deaths due to COVID-19 in the world, most of which could have been avoided and can be credited to negligence of municipal, state, and federal authorities, especially President Jair Messias Bolsonaro. Unfortunately, the country is an example of what not to do in a pandemic setting. Key Points: One year after COVID-19 was declared a pandemic, Brazil had the second higher number of cases and deaths, and the highest number of daily deaths due to the disease. Lack of massive testing, non-stringent and ineffective collective health policies, poor management of the public health care system, and political instability were the main drivers of the country's flawed management of the COVID-19 advancement. Anti-science and sabotaging actions by government had a pivotal role in the country's current situation. Brazil has a large territory and is marked by social contrasts among different regions and states, which showed contrasting data regarding the impact caused by COVID-19. COVID-19 databases and data sharing are important to provide an overview of epidemiological aspects of the disease; however, Brazil lacks standardization in these datasets.